Integrasi Model Kano dan Metode Kansei Engineering untuk Pengembangan Kualitas Layanan Restoran Ayam Goreng di Kota Manado - Johan S C Neyland; Irvan Raymon Rondonuwu; Lidia M Mawikere; Anggiat N P S Nababan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
One of the restaurants that is much loved by various groups is the Kentucky Fried Chicken (KFC) restaurant. This restaurant must maintain its service quality amidst the emergence of new products on the market because customer loyalty is influenced by consumer perceptions of what the restaurant offers. Related to service quality, the purpose of this study is to identify service quality attribute categories using the Kano Model to further analyze customer emotional needs using the Kansei Engineering method in the form of translating customer feelings into service improvement designs. The results of the Kano Model categorization of the service quality of fried chicken restaurants contain 10 attributes in the A (Attractive) category, 9 attributes in the O (One Dimensional) category, and 2 attributes in the I (Indifferent) category, none in the M (Must Be), Q (Questionable), and R (Reverse) categories. From the results of the Kansei Method processing there are 12 Kansei words to represent emotional needs, namely delicious, spacious, slow, long, dirty, fast, clean, delicious, fresh, sea, delicious, extraordinary.